Examining Factors Affecting the Food Expenditure in Indonesia - Mohamad Reza Pahlevi; Dara Yuri Andita; Edwin Gumilar; Febrianti Nursafitri; Sarah Safira Sofiani (Prosiding Industrial Research Workshop and National Seminar, 2018)
The aim of this study is to analyze the effect of Gross Regional Domestic Product, Human Development Index,and the number of family members on the food expenditure in Indonesia. Due to its important role for the familyas well as the community as a whole, managing food expenditure is very important. The management of foodexpenditure is very important. If the main priority of the Indonesian towards food is very high compared to theexpenditures on other things such as travel, saving, or education, it is feared that the quality of their humanresources tend to decline. Thus this research is important. The research explores the three factors from a samplepopulation of 34 provinces in Indonesia in 2015. The causal research was employed and the cross-sectionalmethod was used in this research to gather the data. Also, this research using secondary data from the CentralBureau of Statistics of Indonesia. The result of statistical analysis applying multiple regression shows that theGross Regional Domestic Product has a positive influence on Food Expenditure. In contrast, the other factors suchas the Human Development Index and the number of family members have no significant effect on foodexpenditure.The aim of this study is to analyze the effect of Gross Regional Domestic Product, Human Development Index,and the number of family members on the food expenditure in Indonesia. Due to its important role for the familyas well as the community as a whole, managing food expenditure is very important. The management of foodexpenditure is very important. If the main priority of the Indonesian towards food is very high compared to theexpenditures on other things such as travel, saving, or education, it is feared that the quality of their humanresources tend to decline. Thus this research is important. The research explores the three factors from a samplepopulation of 34 provinces in Indonesia in 2015. The causal research was employed and the cross-sectionalmethod was used in this research to gather the data. Also, this research using secondary data from the CentralBureau of Statistics of Indonesia. The result of statistical analysis applying multiple regression shows that theGross Regional Domestic Product has a positive influence on Food Expenditure. In contrast, the other factors suchas the Human Development Index and the number of family members have no significant effect on foodexpenditure.